2022
DOI: 10.3390/f14010074
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Thinning on Tree Growth and Soil Nutrients in the Middle-Aged Chinese Fir (Cunninghamia lanceolata (Lamb.) Hook.) Plantations

Abstract: Knowing the effect of thinning on forest ecosystem services is an important aspect of sustainable forest management. This study analyzed the traditional thinning on tree growth and soil nutrients in the Chinese fir (Cunninghamia lanceolata (Lamb.) Hook) plantations. The Chinese fir plantations were 11 years old with different initial densities in Jinji (4000 tree·ha−1), and Yingde (3000 tree·ha−1), Xiaolong (2000 tree·ha−1) forest farms, and 20 years old in Yangmei (2000 tree·ha−1) forest farm. The thinning in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Heavy thinning increased pH compared to light and moderate thinning, likely due to higher organic matter mineralization. Similarly, Lin et al (2022) reported that soil pH value increased with an increase in forest canopy openness in Cunninghamia lanceolata (Lamb.) Hook.)…”
Section: Discussionmentioning
confidence: 81%
“…Heavy thinning increased pH compared to light and moderate thinning, likely due to higher organic matter mineralization. Similarly, Lin et al (2022) reported that soil pH value increased with an increase in forest canopy openness in Cunninghamia lanceolata (Lamb.) Hook.)…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, since the Paris climate summit in 2015, forest management has been promoted as an efficient option to increase the accumulation of C by forest ecosystems [11]. Thinning is an essential silvicultural practice widely used in forest management [12], and it has been proved to promote the soil carbon storge of forest ecosystems by altering substrate charateristics [13][14][15][16][17] and the carbon metabolism process rate [18]. For instance, thinning induces more litterfall input, which initially alters substrate availability for microbial, soil enzymatic activity, and carbon mineralization [18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to determine a reasonable stand density under the current site conditions in order to make full use of the forest land productivity and achieve the purpose of promoting the growth of the stand. At present, most of the studies on stand volume and wood quality of Chinese fir plantation thinning are young and middle-aged forests, and the research sites are mainly concentrated in the middle and southern belts of Chinese fir (Tong et al, 2000;Xu et al, 2014;Guo et al, 2019;Lin et al, 2022), but there are relatively few studies on the effects of stand density management in the northern Chinese fir plantation during the cutting age. Here, we analyzed changes in the relationship between the structure and productivity of Chinese fir plantations after thinning.…”
Section: Introductionmentioning
confidence: 99%